Cochrane Database of Systematic Reviews 2007
DOI: 10.1002/14651858.cd006394.pub2
|View full text |Cite|
|
Sign up to set email alerts
|

Nasal saline irrigations for the symptoms of chronic rhinosinusitis

Abstract: Saline irrigations are well tolerated. Although minor side effects are common, the beneficial effect of saline appears to outweigh these drawbacks for the majority of patients. The use of topical saline could be included as a treatment adjunct for the symptoms of chronic rhinosinusitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
47
0
5

Year Published

2009
2009
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(53 citation statements)
references
References 43 publications
1
47
0
5
Order By: Relevance
“…The initial Cochrane systematic review reported benefit of SNI for chronic sinusitis, from eight trials and 399 participants 16. The updated Cochrane review on SNI for chronic sinusitis only included two trials (116 adult participants), due to strict inclusion criteria of randomised controlled trials with a follow-up of at least 3 months 9.…”
Section: Indications and Evidencementioning
confidence: 99%
“…The initial Cochrane systematic review reported benefit of SNI for chronic sinusitis, from eight trials and 399 participants 16. The updated Cochrane review on SNI for chronic sinusitis only included two trials (116 adult participants), due to strict inclusion criteria of randomised controlled trials with a follow-up of at least 3 months 9.…”
Section: Indications and Evidencementioning
confidence: 99%
“…In the case of the neti pot, safety and efficacy are not in question. Nasal irrigation (with or without the neti pot) is well-established as efficacious treatment for chronic sinusitis with few side effects (Harvey et al, 2007). However, studies also show that nasal irrigation may not be effective for acute colds or flus, and there is not enough evidence to recommend its use in these cases (Achilles & M√∂sges, 2013;Kassel, 2010).…”
Section: Neti Pots In Us Media Discoursementioning
confidence: 99%
“…The practice of nasal irrigation (rinsing nostrils using any device) had already been biomedically prescribed for chronic sinus conditions (Harvey, Hannan, Badia, & Scadding, 2007) before neti's recent Neti Pots in US Media Discourse 4 popularity. The neti pot has become one of the most widely-used, natural, and medically effective methods for treating sinus problems (Achilles & M∂sges, 2013).…”
mentioning
confidence: 99%
“…En general, se prefiere usar solución hipertónica, porque tiene aparentemente buen efecto sobre el clearance mucociliar 65,66 . En una revisión sistemática realizada por la base de datos Cochrane (2007) 67 se evaluó el efecto del uso de irrigación salina nasal en la sintomatología de RSC. Fueron seleccionados 8 trabajos que cumplían criterios de inclusión.…”
Section: Lavado Intranasalunclassified